Talitrus saltator as a biomonitor: An assessment of trace element contamination on an urban coastline gradient. Issue 1 (15th July 2017) - Morrison, Liam; Bennion, Matthew; McGrory, Ellen; Hurley, William; Johnson, M.P.
Abstract: This study reports the first ever application of the trace element pollution index (TEPI) along a coastal, urban gradient using trace element concentrations (Ti, Mn, Co, Cu, As, Mo, Ag, Cd, Pb, Cr, Fe, Zn and Se) in the amphipod crustacean Talitrus saltator . S amples were collected from 10 sites in Galway Bay (Ireland) and concentrations of Pb showed the greatest spatial variation, likely due to the proximity of some sites to a former landfill and busy harbour. The TEPI used alongside the quartile method allowed for the assigning of sites to contamination level categories. Mapping these class levels allowed for straightforward visualisation of trace element contamination along the urban gradient. In addition, this study presents trace elements levels in T. saltator form the Atlantic Coast of Europe for the first time and the concentrations observed were comparatively lower than previously reported for T. saltator from the Baltic and Mediterranean seas. Graphical abstract: Highlights: T. saltator as a biomonitor of trace elements contamination along an urban gradient is explored The TEPI and TESVI are applied to concentrations in T. saltator for the first time Locations assigned to contamination-level categories Mapping allowed for visualisation of contamination along an urban gradient North East Atlantic baseline levels for thirteen elements in T. saltator tissue